0054 Metabolite Profiles of Obstructive Sleep Apnea Distinguishes Cases from Controls and Improve With CPAP. (27th May 2020) - Sengupta, A; Lim, D C; Keenan, B T; Keele, L; Pack, A; Weljie, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is a common sleep breathing disorder with significant public health consequences. Despite this, no clinically available objective molecular biomarkers to diagnose, risk stratify and quantify treatment efficiency exist. To this end, high-throughput metabolomics data could serve as a valuable quantitative tool. Methods: We designed a pilot study to investigate the metabolomic effects of OSA and CPAP treatment. Blood serum samples were collected from OSA patients and healthy controls matched with respect to age (±5 years), BMI (±2.5 kg/m 2 ) and gender (N = 20/group). Samples from OSA patients were obtained before and after continuous positive airway pressure (CPAP) treatment. Polar metabolites were analyzed using a targeted ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) metabolomics technique. Results: Supervised multivariate analysis using serum metabolic values of OSA patients and healthy controls showed a significantly different overall metabolic profile between the two groups (orthogonal partial least squares discriminant analysis [OPLS-DA] Q 2 =0.25, p=0.04). Acetylornithine, choline, cytidine, dodecenoylcarnitine, methionine sulfoxide and 3-indoxylsulfate were among the most perturbed metabolites. Major metabolic pathways altered in the OSA patients were methionine and phospholipid metabolism, as well as gut microbial co-metabolism. Lysophosphatidylcholine (16:0), a phospholipid metabolite, demonstrated significant linear association with improved oxygen saturation nadir post CPAP treatment (R 2 = 0.57), suggesting the metabolic features may be used as prognostic clinical biomarkers. Conclusion: These results suggest that OSA significantly impacts blood metabolites, which could potentially be used to establish OSA biomarkers. Moreover, specific metabolic features are associated with post CPAP improvement, such as phospholipids, suggesting a functional association of these metabolites that may help us understand the heterogeneity of OSA. Overall, these results demonstrate the potential of metabolic profiling to develop quantitative molecular markers of OSA. Further studies are underway to validate these findings and investigate the utility of metabolic profiles to objectively measure CPAP efficacy. Support: The work was supported by the program project grant P01 HL094307.